2018
DOI: 10.1002/hpm.2600
|View full text |Cite
|
Sign up to set email alerts
|

The roles of, activities of, and competencies for, community nursing services in rural Vietnam: Implications for policy decisions

Abstract: Community health workforce plays a vital role in providing primary health care services as per the needs of residents; however, few studies have examined how nurses work within commune health centers (CHCs). Using qualitative methods including interviews and focus group discussions with key stakeholders, this study explores the roles, activities, and competencies required of community nursing services in rural districts within Vietnam. Two primary roles were identified: CHC nursing and family nursing. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This study also identified that more than half of all participants did not feel supported by healthcare providers (domain 1) indicating that communication with renal healthcare professionals impacted their ability to know what to do to manage their CKD‐related treatments. As primary healthcare in Vietnam is focused on providing maternal healthcare, childcare, and vaccination services (Huy et al, 2018), for those with chronic diseases, such as CKD, there is little option but to attend outpatient clinics at acute hospitals to have routine follow up (e.g., biochemistry or hematology testing, obtaining repeat prescriptions). There is barely any appointment system for these clinics, so people are often seen by different medical practitioners at each appointment, and they do not have a regular healthcare provider to ask questions about their health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also identified that more than half of all participants did not feel supported by healthcare providers (domain 1) indicating that communication with renal healthcare professionals impacted their ability to know what to do to manage their CKD‐related treatments. As primary healthcare in Vietnam is focused on providing maternal healthcare, childcare, and vaccination services (Huy et al, 2018), for those with chronic diseases, such as CKD, there is little option but to attend outpatient clinics at acute hospitals to have routine follow up (e.g., biochemistry or hematology testing, obtaining repeat prescriptions). There is barely any appointment system for these clinics, so people are often seen by different medical practitioners at each appointment, and they do not have a regular healthcare provider to ask questions about their health.…”
Section: Discussionmentioning
confidence: 99%
“…to know what to do to manage their CKD-related treatments. As primary healthcare in Vietnam is focused on providing maternal healthcare, childcare, and vaccination services (Huy et al, 2018), for those with chronic diseases, such as CKD, there is little option but to attend outpatient clinics at acute hospitals to have routine follow up (e.g., biochemistry or hematology testing, obtaining repeat prescriptions). There is barely any appointment system for these clinics, so people are often seen by different medical practitioners at each appointment, and they do not…”
Section: Discussionmentioning
confidence: 99%
“…Integrated healthcare is more suited to non‐hospital, community‐based care where single‐disease specialists are individually situated, enabling greater cross‐specialty integration and communication to occur. In Vietnam, where community‐based care is largely focused on immunization, maternal health, and childcare (Huy et al, 2018), the only option for people with worsening chronic diseases is to attend acute care hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…health nurse employs knowledge from various fields to promote and protect population health, the subsequent are three core functions: assessment, policy development, and assurance. During assessment, Community health nurse regularly collect and analyze information on health conditions, risks, and resources within the community (Huy et al, 2018). .…”
Section: Communitymentioning
confidence: 99%